OPTIMIZATION OF PLANTING PATTERNS ON PADDY PLOTS IN PURI VILLAGE, PURI DISTRICT, MOJOKERTO REGENCY, EAST JAVA USING A LINEAR PROGRAM - Wiguno, Dwi Prastyo; Saves, Faradlillah (Jurnal Teknik Sipil, 2023)
The research site is located in one of the hamlets in Puri village, which has an agricultural land area of approximately 25 hectares. Because of its fertile soil conditions, the land is very suitable for agriculture. However, the agricultural productivity in Puri village has decreased due to changing weather conditions. Puri village, Puri district, Mojokerto regency, has a flat landscape. The duration of the dry season is slightly longer, affecting the availability of water and causing a change in the initial cropping period. As a result, the cropping pattern in the village is not appropriate, leading to a decrease in agricultural productivity. To solve these problems, an optimal cropping pattern needs to be planned to increase agricultural productivity in the village. In order to plan the optimal cropping pattern, the first thing that needs to be done is to calculate the availability of existing water. Then, the need for irrigation water should be calculated. Using the two sets of calculation data, the optimal cropping pattern can be planned with linear program. The analysis is revealed that Puri village has an optimal cropping pattern with a Paddy-Corn-Corn cropping model and an initial planting period in December period 2.